Pengaruh penerapan e-filing, sanksi perpajakan serta tarif pajak terhadap tingkat kepatuhan wajib pajak orang pribadi dalam melaporkan SPT tahunan (studi empiris di Kantor Pelayanan Pajak Pratama Balikpapan Timur) - Chinndy Ivana; Agus Iwan Kesuma (University of Merdeka Malang, 2023)
This research was conducted to obtain empirical evidence of the relationship between the implementation of e-filing, tax sanctions and tax rates on the level of individual taxpayer compliance in reporting annual tax returns. The type of research used is quantitative research using primary data and for the sample using purposive sampling method with a total of 100 respondents. The data analysis tool uses SEM-PLS assisted by the SmartPLS program version 3.2.9. The results of the analysis show that: (1) the application of e-filing has a significant and positive effect on the level of individual taxpayer compliance in reporting annual tax returns; (2) tax sanctions have a significant and positive effect on the level of individual taxpayer compliance in reporting annual SPT; (3) the tax rate has no effect on the level of individual taxpayer compliance in reporting the annual SPT